2010
DOI: 10.4149/neo_2010_06_522
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of AEG-1 in renal cell carcinoma and its correlation with tumor nuclear grade and progression

Ke Z2,
et al.

Abstract: The study was aimed at detecting the expression of a newly found oncogene, astrocyte elevated gene-1 (AEG-1), in renal cell carcinoma (RCC) and its correlation with histopathologic features and the survival of patients. Real-time reverse transcription-PCR and Western blot showed markedly higher expression of AEG-1 in 8 cases of RCC tissue compared with the paired normal tissue from the same patient. The expression level of AEG-1 was also increased in four RCC cell lines in contrast with normal tubular epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 15 publications
2
40
1
Order By: Relevance
“…An in vitro study by Chen et al (32) investigated the expression of MTDH in four kidney cancer cell lines; 786-0, OS-RC-1, Caki-2 and ACHN. A significantly higher level of MTDH was expressed in these four cell lines in the cytoplasm compared to the HK-2 cells as the control (32).…”
Section: Progression and Survival Of Mtdh In Prostate Cancermentioning
confidence: 88%
See 1 more Smart Citation
“…An in vitro study by Chen et al (32) investigated the expression of MTDH in four kidney cancer cell lines; 786-0, OS-RC-1, Caki-2 and ACHN. A significantly higher level of MTDH was expressed in these four cell lines in the cytoplasm compared to the HK-2 cells as the control (32).…”
Section: Progression and Survival Of Mtdh In Prostate Cancermentioning
confidence: 88%
“…MTDH overexpression in primary kidney cancer has been confirmed by immunohistochemistry, RT-PCR and western blot. Two studies found that the expression of MTDH in kidney carcinoma specimens was high compared to normal tissues (32,33). An in vitro study by Chen et al (32) investigated the expression of MTDH in four kidney cancer cell lines; 786-0, OS-RC-1, Caki-2 and ACHN.…”
Section: Progression and Survival Of Mtdh In Prostate Cancermentioning
confidence: 99%
“…MTDH expression is higher in breast tumors than in normal breast tissue at mRNA and protein level and there is significant association between MTDH expression and each of tumor size, clinical stage and lymph node metastasis [2] . In addition, MTDH expression is higher in renal cell carcinoma than in the paired normal tissue from the same patient and is correlated with tumor grade, clinical stage and TNM classification [5] . Song et al [35] also found that MTDH expression was markedly correlated with TNM classification and histological differentiation in colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 96%
“…Published studies have suggested that MTDH expression is up-regulated in several kinds of tumors, such as breast cancer, prostate cancer, non-small cell lung cancer, squamous cell carcinoma and renal cell carcinoma et al [1][2][3][4][5] and the level of the MTDH expression is associated with tumor invasion and metastasis. Importantly, MTDH enhances the invasiveness of breast cancer cells by inducing epithelial to mesenchymal transition [6] .…”
Section: Introductionmentioning
confidence: 99%
“…AEG-1 is ubiquitously lowly expressed in all normal tissues, with higher expression detected in the skeletal muscle and heart and in endocrine glands such as the thyroid and adrenal gland (22). AEG-1 is markedly upregulated in HCC (16,24), breast (25), gastric (26), gallbladder (27), colorectal (28), prostate (23) and renal (29) cancer, esophageal squamous cell carcinoma (ESSC) (30), non-small cell lung cancer (NSCLC) (31), pancreatic ductal adenocarcinoma (32), tongue carcinoma (33), melanoma (22), glioblastoma multiforme (GBM) (34), acute myeloid leukemia (35), neuroblastoma (36), oligodendroglioma (37) andosteosarcoma (38), cervical (39) and ovarian carcinoma (40).…”
Section: Cloning and Molecular Characteristics Of Aeg-1mentioning
confidence: 99%